PENGARUH GAJI DAN LINGKUNGAN KERJA TERHADAP LOYALITAS KARYAWAN HONORER PADA DINAS PENDIDIKAN KOTA BANJARMASIN - Fajriah, Fauziah; Nurhikmah, Nurhikmah; Dewi, Tusiana (CV. Anugerah Duta Perdana, 2026)
The purpose of this study is to determine the effect of salary on employee loyalty, the effect of work environment on employee loyalty, as well as the simultaneous effect of salary and work environment on the loyalty of honorary employees at the Education Office of Banjarmasin City. The population in this study consisted of 41 honorary employees, and the sampling technique used was total sampling since the population was fewer than 100 individuals; therefore, all members of the population were included as samples. Primary data were collected through questionnaires and analyzed using validity tests, reliability tests, classical assumption tests, hypothesis testing, and multiple linear regression analysis with the assistance of SPSS version 25. Based on the results of this research, it can be concluded that salary has a significant effect on employee loyalty, indicating that fair and appropriate compensation should be maintained to increase employee appreciation and commitment. The work environment also has a significant effect on employee loyalty, which means that improving physical and non-physical work conditions is essential to support employee motivation and comfort. Simultaneously, salary and work environment have a significant influence on employee loyalty, with the work environment being the most dominant factor. Therefore, efforts to improve the work environment and periodically evaluate compensation are necessary to enhance the loyalty of honorary employees at the Education Office of Banjarmasin City.